PET imaging of functional 5-HT1A receptors with [18F]F13640: From PET kinetics modeling to static Standardized Uptake Values Ratio - Pierre Courault; Inés Mérida; Nicolas Costes; Jérôme Redoute; Luc Zimmer; Sophie Lancelot (NeuroImage)
Purpose: F13640 is a highly selective serotonin 5-HT1A receptor ligand with agonist properties identified as a PET radiopharmaceutical candidate. In previous work, we showed the possibility to use long dynamic PET acquisition (225 min) combined with simplified kinetic modelling for [18F]F13640 quantification. In this work, we assessed the feasibility of static acquisition and quantification using standardized uptake value ratio (SUVR) as an alternative. Methods: Test-retest PET-MRI scans of 225 min were conducted in eight healthy male volunteers. For 17 brain regions, distribution volume ratios (DVR) were calculated from the whole kinetics using Logan plot modelling method with the cerebellum white matter as reference region. For the same regions, SUVR were also calculated from static images, for four 20-minute and four 10-minute time-intervals at various time of uptake. Reliability between SUVR and DVR measures were studied, and test-retest parameters were assessed between PET sessions for each time-interval. Results: Reproducibility of measures of SUVR compared to DVR were excellent, whatever the time interval (p < 0.001). For the 20-min. time-intervals, SUVR150–170 showed the best reproducibility and correlation parameters (R2 = 0.95 ± 0.03, intercept = 0.06 ± 0.02, slope = 0.95 ± 0.01). As well, for the 10-min. time-intervals, SUVR150–160 showed the best correlation (R2 = 0.94 ± 0.03, intercept = 0.07 ± 0.02, slope = 0.94 ± 0.01). SUVR reproducibility between test-retest sessions was also excellent for each time-interval. These results were valid for pooled regions as well as at regional level. Conclusion: This study confirms the feasibility of static acquisitions to facilitate clinical use of the [18F]F13640 radiopharmaceutical to image functional 5-HT1A receptors. This involves off-camera injection, 10 to 20 mins static acquisition duration, and quantification using SUVR, while improving patient comfort.